ANALISIS HUKUM KONTEN NEGATIF DI PLATFORM YOUTUBE DI INDONESIA - Laily Indrianingsih; Budiarsih Budiarsih (Gapenas Publisher, 2022)
With the development of information and communication technology followed by the transformation of the spectacle in Indonesia with the development of information and communication media. People are now switching from conventional media such as television and radio to using new media, namely the YouTube platform. On the youtube platform there is no filtering (censorship) of negative content on youtube from an institution authorized to monitor new media that are starting to appear in Indonesia such as on the youtube platform. In this case, the emergence of new media is exceeded freely and worrying. This research will examine the legal protection for viewers against negative content on the Youtube platform in Indonesia as well as digital media surveillance efforts on the Youtube platform in Indonesia. The purpose of this study is to analyze the legal view for viewers of negative content impressions on the Youtube platform in Indonesia and to analyze about digital media surveillance efforts on viewers on the Youtube platform in Indonesia. This research uses normative juridical methods using a statutory approach and a conceptual approach, as well as using primary, secondary and tertiary legal materials.The technique of collecting legal materials is through library research and this research uses qualitative analysis. The results of the study found that KPI as an authorized institution in the field of broadcasting, in this case KPI is not authorized to supervise new social media in Indonesia such as on the youtube platform